Explaining Local Unions’ Responses to Globalization - Foley, Janice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
Twenty-two private sector trade union locals in the manufacturing, service and technology sectors in Canada were surveyed by telephone in 2002/2003. The objective was to determine union locals’ understanding of the impact globalization was having on their operations, and to identify the contextual factors affecting their responses. The data were analyzed qualitatively and quantitatively. The locals associated globalization with plant closures, reduced production, and the elimination of or transfer of jobs and equipment out of the country. Seventeen of the locals reported being affected to a moderate to high degree. Their main responses were lobbying, educating members and the public, and organizing. The important contextual factors identified included local size, industry sector, levels of support available to and accessed by the locals, and the perceived need for and ability to adapt successfully to change.